2020
DOI: 10.21203/rs.3.rs-25146/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Community Psycho-behavioral Responses during the outbreak of novel coronavirus (2019-nCoV): A cross sectional study

Abstract: Background: The novel coronavirus 2019 (2019-nCoV) is a public health emergency of international concern resulting in adverse psychological impacts during the epidemic.The aim of this study: To examine the public’s knowledge and psychological impact during the outbreak of (2019-nCoV) and the extent to which various precautionary measures have been adopted.Materials & Methods: From 1 to 10 April 2020, we conducted an online survey. The online survey collected information on demographic data, precautionary … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Although a study from China reported that neither state nor trait anxiety was associated with COVID-19 preventive behaviours, 5 other recent studies have all linked anxiety with an increased likelihood of engaging in preventive behaviours. 4,9,10 This conflicts with our finding that anxiety symptoms were associated with reduced preventive behaviour. It is uncertain what underlies this difference, but underlines the need for future studies to collect information on the specific causes of anxiety, especially as it has been suggested that high levels of 'health' anxiety might be linked to engaging in excessive preventive behaviour.…”
contrasting
confidence: 95%
“…Although a study from China reported that neither state nor trait anxiety was associated with COVID-19 preventive behaviours, 5 other recent studies have all linked anxiety with an increased likelihood of engaging in preventive behaviours. 4,9,10 This conflicts with our finding that anxiety symptoms were associated with reduced preventive behaviour. It is uncertain what underlies this difference, but underlines the need for future studies to collect information on the specific causes of anxiety, especially as it has been suggested that high levels of 'health' anxiety might be linked to engaging in excessive preventive behaviour.…”
contrasting
confidence: 95%
“…Such worry about infection may lead to preventive behaviors. [23][24][25] In this situation, we found that having general worry about COVID-19 infection did not lead to psychological distress.…”
Section: Discussionmentioning
confidence: 75%
“…However, in this situation, worrying about infection is not unhealthy, but rather, a natural reaction to current events. Such worry about infection may lead to preventive behaviors [23][24][25] . In this situation, we found that having general worry about COVID-19 infection did not lead to psychological distress.…”
Section: Discussionmentioning
confidence: 99%